Biological markers of suicidal behavior and justification of use level calzidiola in the blood - N. N. Petrova; V. V. Dorofeykov; M. V. Dorofeykova; M. S. Zadorozhnaya; I. V. Kaystrya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article is devoted to the problem of search of biomarkers of suicidal behavior and includes literature review, as well as the results of own research of features of suicidal behavior of young age patients with depression (18—27 years) depending on the concentration of calcidiol.